Influence of Taxing System on Business and Tendencies of Estimation - Stačiokas, Romas; Mažeika, Artūras; Šerėnienė, Laima (Ekonomika, 2004)
The main aspects of formation of taxing system after the independence renewal are analysed in this article. Also questions of taxes grouping are observed since 2004 year when a new economical clasification of state and municipalities revenue came into force. Particularly research of tendencies of businessman attitude towards taxes attract most attention (how they value taxing system in various activities and among various size of enterprises).While analyzing taxes in aspect of their influence on natural persons and legal entities it is evident that taxes are constituent of any purposeful production and commercial activity, i.e. business. Everybody has to pay (or must pay) taxes: persons who go for individual economical commercial business and personal business enterprises that develop such activity, also various kinds of partnerships (real, commandite, stock and joint-stock) and budgetary organizations. Revenue (benefit) and added value, wage for employed workers, dividends of shareholders, acquest and so on are taxable by corresponding taxes. It is safe to say that business enterprise paid taxes are the same necessary input such as salaries, cost of goods (services). accounts for home and communal accommodations and so on. Some do not tend to the same reasoning because business also could be developed successfully without any taxation (even financially more marked). That is true because if business enterprises do not pay taxes they would have bigger possibilities for growing up and increasing results of their activities.So, different from other liabilities (that businessman could affect by forecasting implementation of market transactions and dates, negotiating conditions, terms and amounts of financial accounts) of particular business activity establishment and development, taxing liabilities are the most difficult controllable and predictable business liabilities. After all it is impossible to negotiate with government neither that selling extents decreased and it is not enough money to pay taxes nor that rate of tax is too big and payable amount is too large. Practically taxes pierce all economical and commercial business activities (supply, production, realization, marketing, cash flow).Conclusions can be made on accomplished analysis ground that taxes are constituent of any purposeful production and commercial activity, i.e. business and that big taxes block business development. Taxes are a very sensitive field for businessman. Though taxes are constantly reformed, various methods of taxation and tollage are applied, businessman tend to value taxing system more and more sceptical. Negative attitude towards profit (revenue) tax increased among managers of organizations of all kind of activities except for field of financial mediation and transport. Particularly this position is sharp among enterprises that tackle communal, social and personal maintenance activity, also manufacturing and construction. The part of transport and financial mediation enterprises increased that profit tax retarded to develop economical financial activity usefully. The part of health and social work, construction organizations, hotels and restaurants also increased that profit (revenue) kept down. Though number of businessman who marked negative influence of value added tax on their business development rather decreased meantime it reaches almost half of all questioned respondents. Results of research of mentioned influenced reveal that VAT social economical meaning increases lately.